Algorithmic Management and App-based Delivery Workers in Rio de Janeiro - Lucas Souza (Journal of Extreme Anthropology)
The reshaping of global production through platform capitalism has been the subject of numerous studies around the world. Across these, it has been common to observe similar characteristics of this model of management and labour control via algorithmic management. However, it is important to look at the particular facets of each context in the process of platformisation, and food couriers appear as highly relevant agents within this movement. This article investigates how the digitalisation of deliveries has changed work relations and conditions of food couriers in Rio de Janeiro, Brazil, taking into account the connections between AI governance, gender, and race. The argument here is that the platformisation of deliveries has brought greater precarisation to the work of food couriers in Rio de Janeiro, and that this is related not only to the more direct worsening of working conditions as a consequence of the use of apps in the industry, but also to how algorithmic management articulates and incorporates historical issues related to race and gender in this sector of the economy. The article draws on 17 interviews conducted with delivery workers in Rio de Janeiro during the months of August, September, and October 2021, developing a perspective on the platformisation of deliveries through an analysis that considers specific aspects of the reality of Brazil, a country in the Global South, marked by colonial slavery, as well as the gender particularities of its labour market.